Construction waste management: preparedness towards the 4th Industrial Revolution / Jannatun Naemah Ismam, Nurulanis Ahmad @ Mohamed and Nor Azizah Talkis - Ismam, Jannatun Naemah; Ahmad @ Mohamed, Nurulanis; Talkis, Nor Azizah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2018)
Construction waste management (CWM) has progressively improved in a few years, especially in the reduction of waste generated on site and less waste disposal to the landfill. However, there are still a few constraints in operating the waste through the 4R’s concept efficiently. The 4th Industrial Revolution has slowly assimilated into stakeholder engagement in many businesses from various perspectives. The CWM is one of the perspectives in the construction industry that needs emergent response to these evolving trends. Intensive literature review has identified several factors that must be considered by construction practitioners in CWM, mainly for achieving the 4th Industrial Revolution. Furthermore, several technologies applied in different developed countries are reviewed, particularly to explore waste management technology through the 4R’s concept (Reduce, Reuse, Recycle, Remove). This paper has discovered adaptability, the robustness of the technology and accessibility as factors that need to be considered in introducing technology in CWM. The findings give direction to technologists from the public or private organizations in developing proper guidelines of CWM.